ASSOCIATION BETWEEN ACUTE RESPIRATORY DISTRESS SYNDROME (ARDS) INCIDENCE AND INCREASED D-DIMER IN COVID-19 PATIENTS AT BETHESDA HOSPITAL YOGYAKARTA - Hutagaol, Frans Iqlessias; Probowati, Wiwiek; Manus, Widya Christine (Faculty of Medicine Universitas Kristen Duta Wacana, 2024)
Background: Acute Respiratory Distress Syndrome (ARDS) is one of the most common complications of COVID-19 infection and is closely related with patient mortality. Increased D-dimer levels are considered one of the most consistent clinical indicators of coagulopathy. Theoretically, this event is based on the emergence of a cytokine storm triggering lung tissue damage, pulmonary microvascular endothelial damage and alveolar edema, leading to hypoxia in the body. Objective: To determine the association between ARDS incidence and the increase in D-dimer levels in COVID-19 patients at Bethesda Hospital Yogyakarta. Method: This research was conducted in retrospective cohort design. The data utilized in this study came from the medical records of male and female COVID-19 patients between 19 and 60 years old, who were diagnosed with ARDS by doctors at Bethesda Yogyakarta Hospital. The medical records were collected between June 1, 2021, and September 30, 2021. The data analysis included univariate (descriptive statistics) and bivariate (Chi-Square, Mann-Whitney, Spearman Rank) analyses. Result: There was a significant relationship between COVID-19 ARDS patients and the increased levels of D-dimer in patients undergoing hospitalization at Bethesda Hospital Yogyakarta (p<0,001, OR=4,589, 95%CI=2,104-10,007). Additionally, there was a significant difference in D-dimer levels between ARDS and non-ARDS patients. The severity of ARDS, duration of hospitalization, gender, and age did not have a significant association with the increase in D-dimer levels (p>0,05). Conclusion: There was a significant relationship between the incidence of ARDS and elevation of D-dimer levels in COVID-19 patients at Bethesda Hospital Yogyakarta.